Religionisme Ruang di Permukiman Kauman Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
In Java's traditional city a neighborhood called Kauman usually located at the west side of the city great mosque (Masjid Gede), here the clerk of the mosque together with their family live. That is why Kauman neighborhood, in Indonesia's architecture literature, has been known as a mouslem settlement, with a strong religious life. A lot of research has been done focusing on this settlement. This research want to study deeply the experience of the people living in Yogyakarta's Kauman neighborhood. Main material presented in this paper is a description of the people's experience in their daily life, especially their religious aspect, within their built environment. The research uses a phenomenological method, based on Husserlian model. According to IIusserl, the essence of things could be revealed through epoche and some steps of reduction. With the use of this method the researcher has been able to reveale a more rich meaning on the religious life of the people experience in their built environment. For the Kauman people a religious fervour (religionism) does not only present in the worship space but it could present in their entire neighborhood. This space religionism had been created by the continous present of religious activities, atmosphere, and symbols in the daily life of the citizens and which are based on their culture and social history.